A Pragmatic Study of Forms and Functions of Proverbs in Nigeria (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
Thoughts and ideas are consciously or unconsciously conditioned by the culture of a society, and it is almost impossible to use language without a cultural base. One significant aspect of culture is language, and proverbs constitute one of the parameters for gauging the richness of a people's culture. Proverbs are figurative expressions that are usually rich in imagery. In this paper, proverbs across cultures in Nigeria are discussed; in particular, three (3) proverbs each from Hausa, Igbo, and Yoruba cultural environments. The purpose is to examine their literary and linguistic forms, as well as pragmatic functions in Nigeria. The nine (9) proverbs are thus translated into the English language, and analysed by: (1) identifying the figurative expression that each proverb conveys, and (2), employing presupposition to examine the knowledge of the 'world' of the proverbs and their contexts of utterance. The conclusion is that proverbs are in the literary forms of metaphors, aphorisms, and sometimes paradoxes and antithesis. Also, they are employed to perform pragmatic functions of cautioning, warning, satirising, rebuking, etc. in various cultures in Nigeria.
Keywords: culture; proverbs; pragmatics; language; form; function